The health of rural Black communities during COVID: Some affirmations, some surprises - Newman, Sharlene D.; Moss, Kimberly; Pichon, Melonie; Scott, Deborah; Rogers, Kileema; Orr, Angela; Bui, Chuong; Payne-Foster, Pamela (Frontiers in Public Health, 2023)
Background and Objective: There is overwhelming health disparities in the Deep South, including Alabama. It is important to include the voice of communities affected by these disparities when developing interventions. The goal of the current study was to understand the health concerns of five rural communities located in Alabama. Methods: A 15-item health survey was administered in five rural communities in Alabama (N=752). The survey assessed the health concerns and the risky behaviors of the community. Results: In addition to health concerns that were expected (e.g., diabetes and high blood pressure), mental health, aging-related and dental problems were identified as major concerns in the communities. Risky behaviors included alcohol and drug abuse as well as poor eating habits and lack of exercise. Conclusions: The results presented demonstrate that communities are reliable sources of information. They identified health concerns that are easily identified in health data (e.g., diabetes and high blood pressure) as well as concerns not typically discussed in the literature. Additionally, the concerns are community specific making it important to assess individual communities in order to support its residents in improving community health.